Pressure injury screening in the emergency department: A concept analysis. Issue 6 (10th October 2022) - Ogle, Laura; Hand, Mikel W.; Swenty, Constance
Abstract: Aim: This concept analysis analyzes pressure injury screening in the emergency department setting using Walker and Avant's approach. Background: Pressure injury treatment cost in the United States totals over 11 billion dollars annually. Although a pressure injury could develop in the few hours a patient is in the emergency department, there is little guidance on how an emergency department should screen, prevent, and treat patients. Data Source: Five sources resulted from database searches of CINAHL full‐text, Health Business FullTEXT, and MEDLINE with Full Text. Key search terms used to narrow the search consist of the following terminology: "pressure injury" OR "pressure ulcer" AND "screening" AND "risk factors" AND "emergency room" OR "emergency department. Review Methods: Walker and Avant's method of concept analysis was used to clarify the concept of pressure injury screening in the emergency department. Results: The concept analysis identified two attributes of pressure injury screening in the emergency department: patient length of stay and the cost of pressure injury treatment. Antecedents identified are patient risk factors: age, mobility status, sensory perception, comorbidities, and pre‐existing pressure injuries. Positive consequences identified are increased patient comfort, increased staff satisfaction, decreased hospital‐acquired pressure injuries, and increased adherence to established treatment protocols. Conclusions: This concept analysis may help to guide evidence‐based practice for pressure injury screening in the emergency setting. Perhaps screening in the emergency department, if adopted globally, is the missing element needed to finally see a reduction in pressure injury rates.